PENGARUH BERMAIN KONSTRUKTIF TERHADAP KEMAMPUAN EMOSIONAL ANAK USIA 4-5 TAHUN DI TK TIARA DUMAI - Dinda Tri Andriani; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims 1) To know the child's emotional ability before the application of Constructive Playing in TK Tiara Dumai . 2) To know the child's emotional ability after the application of Constructive Playing in TK Tiara Dumai . 3) To know the effect of constructive play to emotional ability of 4-5 years old children in TK Tiara Dumai . This type of research is experimental research. Technique of collecting data which is done through through observation, that is by doing direct observation to location of research to know condition or factor seen at research object. Data analysis techniques used to analyze experimental data using one-pretest posttest design data. In this case the subject of research is 4-5 years old children in TK Tiara Dumai , amounting to 20 children, consisting of 10 men and 10 women. Based on the results of the research, it is known that 1) emotional ability in children aged 4-5 years in TK Tiara Dumai before being given the treatment of constructive playing activities criteria begin to develop the meaning in classical or in general emotional ability is still low that is only obtained percentage value 50,21%. 2) Emotional ability in 4-5 years old children in TK Tiara Dumai after being given the treatment of constructive playing activities criteria developed as expected by means of classical or generally good emotional ability is obtained by the percentage of 75%. 3) The implementation of constructive play in early childhood education learning has a significant effect on emotional ability in 4-5 years old children in TK Tiara Dumai . It can be seen that there are differences in the form of increased emotional ability in children before and after treatment. Constructive play has an effect of 49.79%, on the emotional ability of 4-5 years old children in TK Tiara Dumai .Keywords: Constructive play, emotional ability